2017
DOI: 10.14310/horm.2002.1707
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones: a potential ally to LDL-cholesterol-lowering agents

Abstract: L-thyroxine (LT4) treatment of hypothyroidism, particularly in patients with thyroid- stimulating hormone (TSH) >10mU/L, results in improved lipid profile, as LT4 stimulates low-density lipoprotein cholesterol (LDL-C) degradation and the conversion of cholesterol in bile acids by inducing LDL-receptor and 7 alpha hydroxylase expression, respectively. Statins decrease total cholesterol (TC) and LDL-C mainly by suppressing 3-hydroxy-3-methylglutaryl coenzyme A activity. Therefore, the addition of statins to LT4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…23,24 However, previous studies have shown that hyperlipidaemia and hyperglycaemia are strong independent risk factors for the prognosis of DN, and high-TSH patients in this study had more severe hyperlipidaemia and hyperglycaemia, which might also have contributed to more severe clinical and pathologic changes. Some studies have suggested that thyroid function is significantly associated with alterations in the lipid profile, [25][26][27][28][29] and have proposed SCH as a cause of dyslipidaemia, 30 possibly connected with TSH receptors. 31 In addition, serious SCH might influence glycaemic control in patients with T2DM, 32 while thyroid dysfunction might affect the expression of several glycaemic receptor proteins, 33 suggesting that abnormal levels of thyroid hormones might affect insulin sensitivity in DN patients with deviant blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 However, previous studies have shown that hyperlipidaemia and hyperglycaemia are strong independent risk factors for the prognosis of DN, and high-TSH patients in this study had more severe hyperlipidaemia and hyperglycaemia, which might also have contributed to more severe clinical and pathologic changes. Some studies have suggested that thyroid function is significantly associated with alterations in the lipid profile, [25][26][27][28][29] and have proposed SCH as a cause of dyslipidaemia, 30 possibly connected with TSH receptors. 31 In addition, serious SCH might influence glycaemic control in patients with T2DM, 32 while thyroid dysfunction might affect the expression of several glycaemic receptor proteins, 33 suggesting that abnormal levels of thyroid hormones might affect insulin sensitivity in DN patients with deviant blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…This biological relationship may explain the impact of hypothyroidism, which is often linked to excess TC and low-density lipoprotein cholesterol (LDL-C) [50]. It should be noted that endocrine disorders, including hypothyroidism and type 2 diabetes mellitus, may induce or exacerbate existing dyslipidemia and impede the achievement of optimal results through hypolipidemic drugs [51]. Therefore, CHC patients with dyslipidemia should be regularly checked for thyroid dysfunction, and both cholesterol and its subfractions should be monitored in CHC patients undergoing PEG-IFN/RBV treatment with thyroid failure [49, 51].…”
Section: Discussionmentioning
confidence: 99%
“…Both currently available PCSK9 inhibitors, alirocumab and evolocumab, bind to PCSK9 preventing its binding to the LDLR: this results in continuous LDLR recycling at the hepatic cell surface and clearing of LDL-C particles, causing a decrease in plasma LDL-C concentration ( 95 ). It has been proposed that TH, by stimulating LDLR activity and clearance of LDL-C via PCSK9, may support this mechanism ( 13 ). Also of interest is the fact that the correlation of circulating PCSK9 levels with thyroid function, even in the normal range, may be blunted by obesity ( 96 ).…”
Section: Co-treatment With Statins Ezetimibe and Proprotein Convertmentioning
confidence: 99%
“…Therefore, by thus lowering circulating 5α-stanols while increasing FT3/FT4, presumably by enhancing conversion of T4 to T3, it has the potential to improve thyroid hormone status ( 100 ). It is accordingly suggested that ezetimibe, together with statins, be combined with thyroxine, thereby both ameliorating thyroid function and reducing TC and LDL-C by actively inhibiting the synthesis and intestinal absorption of TC ( 13 ).…”
Section: Co-treatment With Statins Ezetimibe and Proprotein Convertmentioning
confidence: 99%
See 1 more Smart Citation